Growth of Graphene Nanoflakes/h‐BN Heterostructures. Issue 20 (26th September 2021) - Küster, Kathrin; Hooshmand, Zahra; Rosenblatt, Daniel Pablo; Koslowski, Sebastian; Le, Duy; Starke, Ulrich; Rahman, Talat S.; Kern, Klaus; Schlickum, Uta
Abstract: 2D materials such as graphene, hexagonal boron nitride ( h‐ BN), or transition metal dichalcogenides, and their heterostacks are gaining increasing interest because of their extraordinary properties, which can range from superconductivity to large charge carrier mobilities. In this paper, the electronic and structural modifications of h‐ BN on Rh(111) are investigated by the intercalation of carbon forming graphene nanoflakes between the h‐ BN and the Rh(111) surface. The carbon atoms—natural impurities in Rh bulk crystals—diffuse to the surface during the h‐ BN growth and segregate there during cooling. The graphene nanoflakes are present at particular sites under the wires of the h‐ BN nanomesh leading to an altered appearance of the Moiré pattern and modified electronic and chemical properties. Thus, a novel fabrication route of graphene nanoflakes located in a heterostack between Rh(111) and h‐ BN is shown by steering the segregation of carbon impurities at the rhodium surface. Abstract : A 2D heterostack containing graphene nanoflakes at specific sites under a hexagonal boron nitride ( h ‐BN) nanomesh is formed by segregation of carbon, during h ‐BN growth. The graphene nanoflakes change the electronic and chemical properties of the h ‐BN, which is shown theoretically and experimentally by probing the field‐emission resonances and by adsorption of pentacene.